MicroRNA-375 Functions as a Tumor-Suppressor Gene in Gastric Cancer by Targeting Recepteur d’Origine Nantais - Lian, Sen (Int J Mol Sci, 2016)
Emerging evidence supports a fundamental role for microRNAs (miRNA) in regulating cancer metastasis. Recently, microRNA-375 (miR-375) was reported to be downregulated in many types of cancers, including gastric cancer. Increase in the expression of Recepteur d’Origine Nantais (RON), a receptor tyrosine kinase, has been reported in tumors. However, the function of miR-375 and RON expression in gastric cancer metastasis has not been sufficiently studied. In silico analysis identified miR-375 binding sites in the 3′-untranslated regions (3′-UTR) of the RON-encoding gene. Expression of miR-375 resulted in reduced activity of a luciferase reporter containing the 3′-UTR fragments of RON-encoding mRNA, confirming that miR-375 directly targets the 3′-UTR of RON mRNA. Moreover, we found that overexpression of miR-375 inhibited mRNA and protein expression of RON, which was accompanied by the suppression of cell proliferation, migration, and invasion in gastric cancer AGS and MKN-28 cells. Ectopic miR-375 expression also induced G1 cell cycle arrest through a decrease in the expression of cyclin D1, cyclin D3, and in the phosphorylation of retinoblastoma (Rb). Knockdown of RON by RNAi, similar to miR-375 overexpression, suppressed tumorigenic properties and induced G1 arrest through a decrease in the expression of cyclin D1, cyclin D3, and in the phosphorylation of Rb. Thus, our study provides evidence that miR-375 acts as a suppressor of metastasis in gastric cancer by targeting RON, and might represent a new potential therapeutic target for gastric cancer.